Evolution of Phosphorene Sheets through Direct Crystallization of Thin‐Film Red Phosphorus. Issue 2 (17th October 2019) - Rajabali, Mona; Esfandiari, Mehrnaz; Asgharian, Heshmat; Mohajerzadeh, Shams
Abstract : A novel hydrogen plasma treatment to convert an amorphous phosphorus film deposited on silicon substrates into a thin crystalline layer is successfully developed. The amorphous phosphorus layer is deposited on desired substrates as silicon using vacuum evaporation in a direct‐current plasma reactor in a controllable fashion. The formation of 2D phosphorene layers is based on the phase transition of a previously deposited amorphous film into the crystalline black phosphorus flakes. Direct transformation from red phosphorus to black can be achieved at a temperature of 300 °C on desired substrates as silicon, although mica and glass can also be used. This allotrope transformation can be achieved without any high pressure or high temperature. Apart from hydrogen plasma treatment, ultraviolet (UV) exposure to see any possible improvement in the 2D layer formation is also used herein. Various characterization techniques including scanning electron microscopy, transmission electron microscopy, atomic force microscopy, and Raman spectroscopy are used to study the crystallinity and morphology of the samples. In addition, the plasma‐treated flakes are used to realize photodetectors which show excellent response to illuminating light. While the hydrogen plasma treatment leads to crystalline phosphorene sheets, the UV treatment results in granular and partially crystalline nanostructures. Abstract : Direct formation of phosphorene sheets on silicon substrates using hydrogen plasma treatment is conducted. The energy imparted from hydrogen ions leads to rearrangement of phosphorus atoms and results in a layered structure. Raman spectroscopy and electron microscopy corroborate the evolution of crystalline films. A photodevice is realized with these sheets, showing suitable photoresponse.